Effects of NO3-/NH4+ ratios on growth, enzyme activity and nitrogen assimilation-related gene expression in Toona sinensis seedlings - Xiaopu SHI; Taotao SHAO; Beibei MA; Juan WANG; Mingqin FAN; Hu ZHAO (Biologia Plantarum)
Nitrogen is an essential nutrient for plants. Different nitrate (NO3-)/ammonium (NH4+) ratios have different effects on plant growth. However, the underlying mechanism in Toona sinensis remains unclear. Thus, we determined the effects of five different NO3-/NH4+ ratios (16/0, 12/4, 8/8, 4/12, and 0/16, denoted T1, T2, T3, T4, and T5, respectively) in nutrient media on T. sinensis seedling growth. When the nitrogen source was NH4+ alone (T5) or NO3- alone (T1), the soluble protein content in the leaves was the lowest. Additionally, the activities of key nitrogen assimilation-related enzymes, such as nitrate reductase (NR), glutamate synthase (GOGAT), and glutamine synthetase (GS), were altered by the NO3-/NH4+ ratio. Principal component analysis (PCA) revealed that the T2 treatment was optimal for T. sinensis seedling growth. The NO3-/NH4+ ratio regulates nitrogen assimilation at the transcription level, as under high NO3- conditions, the expressions of NR, GS, and NADH-GOGAT were high, and nitrate transporter (NRT) family members NRT1, NRT1.1, and NRT1.7 played leading roles in nitrogen transport. However, under low NO3- conditions, the level of NRT2.7 increased to ensure nutrient absorption. Our results provide a theoretical basis for understanding how different NO3-/NH4+ ratios affect T. sinensis growth.